AB1158 Prevalence of comorbidities in psoriatic arthritis: a cross-sectional study. (15th June 2017) - Gudu, T; Peltea, A; Abobului, M; Balanescu, A; Berghea, F; Bojinca, V; Borangiu, A; Constantinescu, C; Groseanu, L; Negru, MM; Opris-Belinski, D; Predeteanu, D; et al.
Abstract : Background: Psoriatic arthritis (PsA) is associated with important comorbidities: cardiovascular, gastro-intestinal, infectious, malignant, and psychiatric [1, 2]. However, they are less studied in PsA compared to other chronic inflammatory arthritis. Objectives: The objective of this study was to calculate the prevalence of comorbidities and risk factors in a cohort of PsA patients. Methods: This was an observational cross-sectional study, including consecutive, unselected adult patients, with a diagnosis of PsA according to their rheumatologist. Data collected: demographical, clinical (affected joints, current psoriasis, axial involvement, enthesitis, dactylitis), biological (acute phase reactants), and treatment related (nonsteroidal anti-inflammatory drugs, synthetic remissive drugs and biologics). Data on comorbidities and risk factors were collected according to the European League Against Rheumatism (EULAR) recommendations on reporting comorbidities in chronic inflammatory rheumatic diseases in daily practice [3]. Results: In all, 129 PsA patients were included: 77 (59.7%) women, mean age ± standard deviation 53.5±11.8 years, disease duration 7±7.4 years; 53 (41.1%) had axial involvement, 33 (25.6%) dactylitis, 18 (14%) enthesitis, and 24 (18.6%) current moderate/severe psoriasis. Most of them had low or moderate disease activity and almost a quarter of them (32; 24.8%) were taking a biologic. The most prevalent comorbidities were: dyslipidaemia 103 patients (79.8%), hypertension 67 (51.9%), obesity 44 (34.1%), diabetes 21 (16.3%) and ischemic heart disease 15 (11.6%). Almost a third of patients (42, 32.6%) suffered a cardiovascular event after their PsA diagnosis, of which heart attack 2 patients, stroke 4, cardiac failure 4 and peripheral arterial disease one patient. Cardiovascular events correlated with smoking (r=0.893, p<0.001) and current moderate/severe psoriasis (r=0.218, p=0.013). Regarding infectious comorbidities: 11 patients (8.5%) had a history of tuberculosis after being diagnosed with PsA, 7 (5.4%) chronic viral hepatitis, of which 4 with B virus and 3 with C virus, and 5 patients (3.9%) developed severe infections. Five patients (3.9%) were diagnosed with neoplasia, but no correlation was identified with any of the clinical, biological or treatment related included variables. Only 11 patients (8.5%) were diagnosed with depression, but the prevalence is probably underestimated, since not all patients were screened to this end. Conclusions: PsA is associated with a high prevalence of comorbidities, especially cardiovascular diseases. This should be taken into consideration in the therapeutic and the global management of PsA patients. References: Husni ME, Mease PJ. Managing comorbid disease in patients with psoriatic arthritis. Curr Rheumatol Rep 2010;12(4):281–7. Ogdie A, Yu Y, Haynes K, et al. Risk of major cardiovascular events in patients with psoriatic arthritis, psoriasis and rheumatoid arthritis: apopulation-based cohort study. Ann Rheum Dis 2015;74(2):326–32. Baillet A, Gossec L, Carmona L, et al. Points to consider for reporting, screening for and preventing selected comorbidities in chronic inflammatory rheumatic diseases in daily practice: a EULAR initiative. Ann Rheum Dis 2016;75(6):965–73. Disclosure of Interest: None declared